Social Behavior of Antibiotic Resistant Mutants Within Pseudomonas aeruginosa Biofilm Communities - Rojo-Molinero, Estrella; Macià, María D.; Oliver, Antonio (Frontiers in Microbiology, 2019)
The complex spatial structure and the heterogeneity within biofilms lead to the emergence of specific social behaviors. However, the impact of resistant mutants within bacterial communities is still mostly unknown. Thus, we determined whether antibiotic resistant mutants display selfish or altruistic behaviors in mixed Pseudomonas aeruginosa biofilms exposed to antibiotics. ECFP-tagged P. aeruginosa strain PAO1 and its EYFP-tagged derivatives hyperproducing the β-lactamase AmpC or the efflux pump MexAB-OprM were used to develop single or mixed biofilms. Mature biofilms were challenged with different concentrations of β-lactams to monitor biofilm structural dynamics, using confocal laser scanning microscopy (CLSM), and population dynamics, through enumeration of viable cells. While exposure of single wild-type PAO1 biofilms to β-lactams lead to a major reduction in bacterial load, it had little effect on biofilms formed by the resistant mutants. However, the most reveling finding was that bacterial load of wild-type PAO1 was significantly increased when growing in mixed biofilms compared to single biofilms. In agreement with CFU enumeration data, CLSM images revealed the amplification of the resistant mutants and their protection of susceptible populations. These findings show that mutants expressing diverse resistance mechanisms, including β-lactamases, but also, as evidenced for the first time, efflux pumps, protect the whole biofilm community, preserving susceptible populations from the effect of antibiotics. Thus, these results are a step forward to understanding antibiotic resistance dynamics in biofilms, as well as the population biology of bacterial pathogens in chronic infections, where the coexistence of susceptible and resistant variants is a hallmark.